Measuring the violence and incivility of players in professional sport and the disciplinary bodies` management: statistical analysis of French professional football - Ruppé, W.; Sirost, O.; Durand, C.; Dermit, N. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
This paper presents the results of a statistical analysis of the violence and incivility of professional football players on and around the field and how the disciplinary bodies manage these phenomena. The sanctions issued by the disciplinary committees were examined with the objectives of (i) empirically determining the distribution of sanctioned behaviours and their evolution, and (ii) evaluating how these infringements on sporting ethics were handled. The 6027 observations collected from professional football competitions in France over ten seasons (2007-2008 to 2016-2017) highlight contrasting changes in sanctioned violence and incivilities and show that the disciplinary code was not fully applied in certain subcategories.